Caregiver Views and Practices Regarding Children's Antibiotic Suspensions in Lebanon - Sonji, Ghassan M.; Sonji, Nada M.; Boukhary, Rima; Hodeib, Fadi; Majzoub, Mohammad S.; Assi, Mohammad (Jordan Journal of Pharmaceutical Sciences, 2025)
Lebanon grapples with the pressing challenge of pediatric antibiotic misuse. To tackle this issue, we conducted a cross-sectional study in Beirut aimed at assessing caregivers' knowledge and practices regarding children's antibiotic suspensions. A total of 113 caregivers were interviewed at pharmacies to evaluate their comprehension of medication instructions, dosing accuracy, storage/disposal practices, and satisfaction with pharmacist counseling. Results indicated that while 67.3 % of caregivers demonstrated a clear understanding of medication instructions and 63.7 % followed proper reconstitution, concerning practices surfaced. Notably, 71.7 % of caregivers stored leftover suspensions in kitchens. However, 56.6 % correctly disposed of them. Widespread use of cold mineral water as a diluent (66.4 %) contradicts guidelines. Pharmacists played a crucial role, with 69.1 % of caregivers receiving counseling, yet averaging only 3.7 minutes, suggesting room for improvement. Significant correlations emerged between accurate understanding and proper reconstitution (p < 0.001). These findings highlight the need for clearer instructions for caregivers, educational initiatives on appropriate storage and disposal, and enhanced training for pharmacists. Addressing these aspects can improve health outcomes in Lebanon and contribute to the global fight against antibiotic resistance.